2015
DOI: 10.2174/1874613601509010089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Exercise in HIV + Mozambican Women Using Antiretroviral Therapy

Abstract: The aim of this study was to evaluate and compare the effect of two types of exercises interventions on the regularity and health-related physical fitness in HIV-infected individuals who use antiretroviral therapy (ART). A total of 53 HIV+ African women (mean age=39.5±8.4 years) on ART participated in the study. Subjects were randomly divided into 3 groups, namely, formal exercise (FEG), playful exercise (PEG) and control (CG). During 12 weeks, the exercise groups underwent a program of 1-hour duration with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In addition, Terry et al [74], included flexibility exercise. Seven (7) studies utilized Resistant exercises [36, 68–70, 73, 75, 77]. In addition, four studies [36, 68, 70, 77] included flexibility exercise.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Terry et al [74], included flexibility exercise. Seven (7) studies utilized Resistant exercises [36, 68–70, 73, 75, 77]. In addition, four studies [36, 68, 70, 77] included flexibility exercise.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and application of the eligibility criteria, 21 studies (Baigis et al, 2002;Cade et al, 2003;Cade et al, 2013;Cutrono et al, 2015;Dolan et al, 2006;Ezema et al, 2014;Hand et al, 2008;Jaggers et al, 2014;MacArthur et al, 1993;Mangona et al, 2015;Mapstone et al, 2014;Mutimura et al, 2008;Neto et al, 2016;Oursler et al, 2009;Perna et al, 1999;Ramírez-Marrero et al, 2014;Raso et al, 2013;Smith et al, 2001;Sullivan et al, 2014;Terry et al, 2006;Thoni et al, 2002) were eligible for inclusion in the meta-analysis. (n=31) and sub-maximal (n=5) exercise tests.…”
Section: Search Results and Flow Of Studies Through The Reviewmentioning
confidence: 99%
“…For example, in a Nigerian study15 45 to 60 min, 3 times/week for 8 weeks moderate intensity exercise (n=17) resulted in reduced blood pressure levels, improved aerobic fitness and increased CD4 cells versus conventional therapy involving anti-retroviral therapy and counseling only (n=16). Mangona et al16 demonstrated in a community setting in Mozambique that a 13 weeks aerobic and resistance training program incorporating 20 minutes of cycling at moderate to high intensity and a muscular endurance circuit consisting of 6 exercises at 15 repetitions per minute resulted in improved cardiorespiratory fitness (n=19). Mutimura et al17 on their turn showed that a 6-month supervised exercise program (3 times per week during 90 minutes) (n=50) at a fitness club in Kigali, Rwanda resulted in more social relationships, an improved quality of life, a better self-esteem and body image and less emotional stress than in the control group receiving care as usual.…”
Section: Introductionmentioning
confidence: 99%